PENGARUH TERAPI BEKAM KERING TERHADAP HIPERTENSI PADA REMAJA AKHIR DI DESA SUKAMAJU RW 11 RW 12 KABUPATEN CIANJUR TAHUN 2024 - Selin Berliana; Irma Herliana; Ns Solehudin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Hypertension is a disease that attacks many people of all ages, one of which is teenagers. The danger of hypertension for teenagers is that they are susceptible to heart disease in the future. Objective: This study aims to determine the effect of dry cupping therapy on hypertension sufferers in adolescents in the area of Desa Sukamaju RW 11 and RW 12 Cianjur Regency in 2024. Method: This research uses a quantitative experimental research method using a quasi-experimental design with pre and post using a one group pre test and post test design. Research Results: The population in this study was elderly people suffering from hypertension in the Sukamaju Village area, Cianjur District, Cianjur Regency with a sample of 18 people. Data collection techniques by observation. The analysis used is Univariate and Bivariate using the paired sample T test. Conclusion: The blood pressure of hypertensive patients before being given the dry cupping therapy intervention was obtained by information on the Mean Arterial Preasure) intervention value, the mean value was 129.39 mmHg, and after being given the dry cupping therapy intervention, the mean value was 93.06 mmHg. That there was a therapeutic effect. dry cupping against hypertension in late adolescents in Sukamaju Village RW 11 and RW 12 Cianjur Regency in 2024